RELATIONSHIP BETWEEN POSTPARTUM ANXIETY AND BABY BLUES SYNDROME AT UNIVERSITAS AIRLANGGA HOSPITAL - Intan Fairuz Zakia; Izzati, Dwi; Atika, Atika (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Postpartum mothers are vulnerable to mental health problems, including baby blues syndrome, which occurs in the first week. Baby blues syndrome has the potential to predict postpartum depression, and if left untreated, it can lead to more severe mental disorders. This study aims to determine the relationship between the level of postpartum maternal anxiety and the occurrence of baby blues syndrome at Universitas Airlangga Hospital. Method: This was a quantitative study with an observational analytic method and a cross-sectional design. The population in this study was mothers 1-2 days postpartum who were treated at Universitas Airlangga Hospital in December 2023. The study involved 33 postpartum mothers sampled using the consecutive sampling method. The instruments used were questionnaires, the Perinatal Anxiety Screening Scale (PASS) to measure anxiety and the Edinburgh Postnatal Depression Scale (EPDS) to measure symptoms of baby blues syndrome. The analysis method used was the chi-square test. Results: Respondents with anxiety without symptoms were 12 (36.36%), none of whom experienced baby blues syndrome. Out of 16 respondents with mild to moderate anxiety and experienced baby blues syndrome, one person (3.03%) did. And out of 5 respondents with severe anxiety and experienced baby blues syndrome, one person (3.03%). The p-value of 0.289 based on the chi-square test. Conclusion: The level of anxiety in postpartum mothers is not related to the incidence of Baby Blues Syndrome.